Influence of pre-hospital to post-hospital delay factors on MI complications: a prospective cohort study - Javeria Akhter; Khalid Naseeb; Sameera Ali (Journal of the Pakistan Medical Association)
Objective: To identify factors contributing to delays in in the initiation of treatment among ST elevation myocardial infarction patients.